Respiratory Strategies in Relation to Ecology and Behaviour in Three Diurnal Namib Desert Tenebrionid Beetles - Frances D. Duncan (Insects, 2021)
The respiratory physiology of three diurnal ultraxerophilous tenebrionid beetles inhabiting either the dune slipface or gravel plain in the Namib Desert was investigated. The role of the mesothoracic spiracles and subelytral cavity in gas exchange was determined by flow-through respirometry. All three species exhibited the discontinuous gas exchange cycles with a distinct convection based flutter period and similar mass specific metabolic rates. There was variation in their respiration mechanics that related to the ecology of the species. The largest beetle species, Onymacris plana, living on the dune slipface, has a leaky subelytral cavity and used all its spiracles for gas exchange. Thus, it could use evaporative cooling from its respiratory surface. This species is a fog harvester as well as able to replenish water through metabolising fats while running rapidly. The two smaller species inhabiting the gravel plains, Metriopus depressus and Zophosis amabilis, used the mesothoracic spiracles almost exclusively for gas exchange as well as increasing the proportional length of the flutter period to reduce respiratory water loss. Neither species have been reported to drink water droplets, and thus conserving respiratory water would allow them to be active longer.